Influencing factors to E-Wallet adoption among generation Z / Siti Nuraisyah Abd Razak ... [et al.] - Abd Razak, Siti Nuraisyah; Ghazali, Nurdia Azlin; Shakarudin, Nur Aishah; Zalaruddin, Muhammad Nur Iqbal (2021)
E-wallet usage is very popular and advancing in recent years, especially in Malaysia. Users have shifted from cash to electronic payment methods due to the advancement of technology as well as to adapt to the new lifestyle because of pandemic Covid-19. The enforcement of the Movement Control Order due to the Covid-19 outbreak has changed users liking to the ease of contactless payment and it increases the usage of an e-wallet (Izwan Ismail, 2021). E-wallet or electronic wallet is one type of payment that allows users to send or receive payment online through any digital device to buy or sell products. This method of payment is widely accepted at the physical store as well as an online store. By using an e-wallet, users do not have to bring a lot of cash when shopping and they just need to store money in an e-wallet at the same time they can decrease the number of interactions with others. The increasing demand for electronic payment in Malaysia can be seen through the development of various kinds of e-wallet by digital market service providers such as Touch n Go ewallet, boost, GrabPay, and Lazada wallet. Many e-wallet providers offer interesting benefits such as vouchers and cashback to attract users from different ranges of ages to use the e-wallet. Generation Z is known as a generation with most particularly savvy with technology as they grew up with technology and the internet. Generation Z refers to the generation that was born between 1997 and 2012 (Dimock, 2019) and the oldest among this generation is just turning 24 in 2021. Using an ewallet is incredibly convenient; however, there are always risks for users especially young buyers. Despite the risk, this young generation always wants to explore and experience this new payment method and its convenience, and security (Wood, 2013). This study will look at the factors that influence this young generation in adopting e-wallet.